1998
DOI: 10.1562/0031-8655(1998)067<0090:teobso>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biological Substrates on the Ultrafast Excited-state Dynamics of Zinc Phthalocyanine Tetrasulfonate in Solution

Abstract: Zinc phthalocyanine tetrasulfonate (ZnPcS4), a potential photosensitizer for photodynamic therapy (PDT), has been studied using femtosecond laser spectroscopy. The excited-state dynamics in water have been found to be fast (< 80 ps) and dominated by intermolecular aggregation. Since the proposed mechanism for PDT is energy transfer from the triplet excited state of the photosensitizer to triplet O2 creating singlet O2, the short lifetime is expected to be unfavorable for producing singlet O2. This leads to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
8
0
5
Order By: Relevance
“…It has been shown that aggregation changes the photophysical properties of porphyrin, chlorin, and phthalocyanine photosensitizers [85][86][87][88][89][90][91][92][93][94][95][96]. Aggregation shortens the triplet-state lifetime and decreases the singlet-oxygen quantum yield by dissipating the energy through internal conversion [92][93][94][95][96][97]. Therefore highly aggregated photosensitizers in vivo are generally considered to be less effective photosensitizers [87,98].…”
Section: Amphiphilicitymentioning
confidence: 99%
“…It has been shown that aggregation changes the photophysical properties of porphyrin, chlorin, and phthalocyanine photosensitizers [85][86][87][88][89][90][91][92][93][94][95][96]. Aggregation shortens the triplet-state lifetime and decreases the singlet-oxygen quantum yield by dissipating the energy through internal conversion [92][93][94][95][96][97]. Therefore highly aggregated photosensitizers in vivo are generally considered to be less effective photosensitizers [87,98].…”
Section: Amphiphilicitymentioning
confidence: 99%
“…Photodynamic therapy is a promising treatment of cancer and nonmalignant diseases such as skin [3], lung, head and neck [4], liver [5], bladder [6], esophageal [7] and breast cancer [8], brain tumors [9] and sterilization of blood to eliminate viruses such as HIV and hepatitis for transfusion [6]. This medical treatment modality is based on the localization of a chemical photosensitizer in the target cells followed by light irradiation at certain wavelength that corresponds to the peak absorption of the photosensitizer into the target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[53] . citocromo e várias enzimas do tipo oxidases [54] . Assim, as ftalocianinas podem ser reconhecidas como moléculas biomiméticas, onde podem substituir convenientemente proteínas naturais, atuando como o centro ativo de moléculas enzimáticas, com a mesma seletividade e sensibilidade [55] .…”
Section: Nanotubos De Carbonounclassified